Kontruksi Hukum Islam pada Undang-Undang Jaminan Produk Halal Perspektif Maqashid Syariah (Undang-Undang No. 33 Tahun 2014 dan Undang-Undang No 11 Tahun 2020 Pasal 48) - Fachri Fachrudin; Sujian Suretno; Muslim; Ade Kohar; Agus Mailana (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This article describes the construction of Islamic law on the halal product guarantee law that applies in Indonesia. The shifting of operators in halal product guarantees from private institutions to the government has strong legitimacy, which requires business actors to comply. The status of halal certification has increased from voluntary to mandatory in line with the 1945 constitution, and Sharia principles should be achieved. However, the weakness of this law is that there are no strict sanctions for business actors who need to certify their products. This type of research is an explanatory qualitative with a mashed Sharia approach and a review of Islamic law. The research findings show that Sharia obligations that do not contain legal sanctions cause individuals or groups not to comply; this has implications for Muslim consumers being unprotected from the need for halal products because there are still many products that are not halal certified. In conclusion, the construction of Islamic law regarding the guarantee of halal products in Indonesia is still weak but better than before.